Advertising Competition in Retail Markets - BAGWELL, Kyle (Institutional Knowledge at Singapore Management University, 2010)
We consider non-price advertising by retail firms that are privately informed as to their respective production costs. We construct an advertising equilibrium, in which informed consumers use an advertising search rule whereby they buy from the highest-advertising firm. Consumers are rational in using the advertising search rule, since the lowest-cost firm advertises the most and also selects the lowest price. Even though the advertising equilibrium facilitates productive effi ciency, we establish conditions under which firms enjoy higher expected profit when advertising is banned. Consumer welfare falls in this case, however. Under free entry, social surplus is higher when advertising is allowed. In addition, we consider a benchmark model of price competition; we provide comparative-statics results with respect to the number of informed consumers, the number of firms and the distribution of costs; and we consider the possibility of sequential search